Pivotal Role of Multishelled Architecture in Nanoreactor with Spatial Confined Co3O4 for Peroxymonosulfate Activation and Contaminants Degradation - Geng Li; Shiyu Bian; Wenting Sun; Yuwei Pan; Weinan Xing; Ying Zhang; Guangyu Wu; Yudong Huang (Small Structures)
In recent years, cobalt‐based catalysts have been widely used in advanced oxidation technology to degrade pollutants in water environments. However, the reasons for the improved efficiency and performance of cobalt‐based catalysts with different shapes and structures on the activation of persulfate for contaminant degradation are still largely unknown. This study constructs different shapes and structures of cobalt‐based catalysts, namely, Co3O4 nanosphere, multishelled Co3O4 nanosphere (MSCONS), Co3O4 nanocube and multishelled Co3O4 nanocube, in combination with persulfate activation, on the degradation of tetracycline (TC) and bisphenol A (BPA), representative substances of antibiotics and endocrine disruptors in water environments. Batch experiments exhibit satisfactory TC (96.3%) and BPA (98.5%) degradation efficiency under MSCONS/peroxymonosulfate. Furthermore, MSCONS exhibits wide applicability under complex water matrix conditions. Consequently, an integration of density functional theory computations and intermediates analysis demonstrates that the synergy, rather than the isolated effects of radical and nonradical active species, broadens the degradation pathways of TC and BPA, thereby improving the removal efficiency. Overall, this study offers novel insights into the factors contributing to the enhanced performance of cobalt‐based catalysts with varying shapes and structures. Additionally, it proposes new research avenues for investigating the effects of shapes and structures on other transition metal‐based catalysts.